INTEGRATED VECTOR MANAGEMENT: PANACEA FOR MALARIA CONTROL - Charles C. Onoh,; Justin K. Aguocha,; Rose N. Nwabueze, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2020)
Integrated vector management (IVM) is a selective application of numerous control measures and management techniques either simultaneously or sequentially for effective control of vectors. It is a technique for managing vector populations in the bid to mitigate or interrupt transmission of diseases. IVM is based on the presupposition that proper control is not the exclusive responsibility of the health industry but needs the joint efforts of many other agencies, community interest and involvement. Existing literature on the Review article were retrieved through Google Scholar, PubMed, Journals, Personal communication and elibrary searches, and the literature reviewed. Taking Anopheles mosquito as an example, the bionomics of an anopheles mosquito starts from:Egg → Larva → Pupa → AdultThe main objective of IVM is to avert the transmission of vector-borne diseases like malaria. An effective mosquito control measure should encompass: environmental, chemical, biological and genetic control measures.The IVM through its Global Strategic Framework should be developed to tackle various insufficiencies and frailties in vector control and to enhance the efficacy, cost-effectiveness, ecological soundness and sustainability. There must be emphasis on the promotion of interdisciplinary integration and inter-sectoral cooperation between relevant stakeholders at all levels.